Pedagogical research in the practicum at universidad nacional: efl pre- service teachers’ conceptions and experiences (2008)
This study took place at Universidad Nacional de Colombia in the Foreign Languages Department. Concerns coming from the area of pedagogy and teaching Practice guided our efforts to seek opportunities to uphold pedagogical research as an enriching component for the preparation of prospective teachers in EFL (English as a foreign language). Student teachers, who had studied the basis of pedagogical research, planned and implemented projects to solve problematic situations along their practicum. After analyzing participants’ testimonies, results provided valuable information in relation to the conceptions student teachers held towards research as well as the professional attitudes they seemed to develop. Likewise, this study evidences how conducting research posed several challenges for these future teachers.Key words: Pedagogical research, foreign language classroom, pre-service teachers’ preparation, teachingpracticumEste estudio se llevó a cabo en el Departamento de Lenguas Extranjeras de la Universidad Nacional de Colombia. Inquietudes surgidas de las áreas de pedagogía y práctica docente nos motivaron a buscar oportunidades para hacer de lainvestigación pedagógica en la enseñanza y el aprendizaje del inglés como lengua extranjera un componente enriquecedor enla preparación de futuros docentes. Estudiantes practicantes que conocían las bases de la investigación pedagógica,planearon e implementaron proyectos para resolver situaciones problemáticas a lo largo de su práctica. Después de analizarlos testimonios de los participantes, los resultados revelaron información importante respecto a la forma como los futurosdocentes concebían la investigación y las actitudes profesionales que éstos parecían adoptar. Además, este estudio proporciona datos relacionados con los retos asumidos por estos futuros profesores al involucrarse en investigación.Palabras Clave: Investigación pedagógica, salón de lenguas extranjeras, preparación de estudiantes-profesores, práctica docente.